Effects of Pursed Lip Breathing with Arm Ergometry after Chin Support Position in Copd Patients - Mashaal Rana, Muhammad Iqbal Tariq, Anayatullah Syed, Uffaq Zeb, Farrakh Tariq, Aqsa Tahir, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: COPD is the 4th leading cause of mortality around the globe and is expected to be the 3rdleading cause of mortality by 2020. It is a life limiting condition with symptoms of distress such as dyspnea, fatigue, pain and depression as it reaches the terminal stage. The condition decreases the pulmonary function values and QoL. Aerobic training and breathing maneuvers are essential components of pulmonary rehab improving pulmonary function values and QoL. Objective: To find out the effects of pursed lip breathing with arm ergometry after chin support position on respiratory parameters, spirometry tests and quality of life in patients of COPD.. Methods: It was a Randomized control Trial conducted on mild to moderate stage COPD patients. Purposive sampling was used to gain the study sample and then allocated randomly into two groups by coin toss method. The sample size calculated was 74 with 37 subjects in control group and 37 subjects in interventional group. It was conducted at Rehman Medical Institute Peshawar. Spirometer Testing (FEV1,FVC,PEF), HR,SPO2, RR, BORG dyspnea scale and CAT questionnaire were used as outcome measures to measure breathlessness and QoL respectively. Results: Mann-Whitney U test was used between the two groups to measure the effect of the two interventions. There was significant difference between group results (p-value<0.05) were found post-intervention for HR, FEV1, FVC, PEF, BORG score and CAT score. Freidmann test was used for within group analysis and reported significant results (p-value >0.05) for RR, oxygen saturation along with significant BORG and CAT results. Conclusion: It was concluded that there were significant effects of pursed lip breathing with arm ergometry after chin support position on respiratory parameters, spirometry tests and QoL in patients with COPD. Keywords: Chin Support Position, Arm Ergometry, Oxygen Saturation.